Efektivitas Penggunaan Media Sosial sebagai Media Promosi Wisata Umbul Ponggok, Kabupaten Klaten - Wanda Fazriah Oktaviani; Anna Fatchiya (Jurnal Komunikasi Pembangunan, 2019)
Umbul Ponggok tourism manager conducts promotional activities through social media such as instagram and website. Managers hope that utilizing social media as a media campaign can attract public to visit. The purpose of this study is to analyze the characteristics of respondents and social media, to analyze the extent of the effectiveness of social media, also what factors influence the effectiveness of promotion. The location of this study is in Ponggok Village, Polanharjo District, Klaten Regency, Central Java with total number of respondents was 30 from website and 85 from instagram. This study uses a quantitative approach with an online questionnaire instrument and is supported by qualitative data. The results showed the majority of respondents who accessed social media of Umbul Ponggok namely women, average 21 years old as S1 students with an average expenditure of Rp 2,756,000 per month and originating from West Java / DKI Jakarta. Respondents considered information on social media was clear and complete. The use of social media is very effective at the stage of interest and desire. The factors that influence the effectiveness of promotion at interest level are income and completeness of information, in desire level are information clarity and attractiveness, while on action level are the level of income and completeness of information.